keseimbangan hidup dunia dan akhirat : Konsep Mewujudkan Keseimbangan Hidup dunia akhirat - sholihah, mar'atus; Nailil , Novita; Rahmawati, Ana (Universitas Islam Syekh-Yusuf, 2024)
According to Islamic education, human life consists of 2 main components, namely: worldly life that leads to material aspects and spiritual life that leads to moral aspects, which lead to happiness and well-being in the hereafter. Therefore, Islamic education is needed to help humans achieve their goals both in the world and in the hereafter, because the Islamic view is universal and covers all aspects of life. Therefore, the key to happiness in life is the ability to balance worldly life and the hereafter. This balance can be achieved through life education, which means considering worldly life as a means to go through eternal life in the hereafter.